ChemInform Abstract: Catalytic Enantioselective Synthesis of N, Cα, Cα‐Trisubstituted α‐Amino Acid Derivatives Using 1H‐Imidazol‐4(5H)‐ones as Key Templates. Issue 40 (October 2015) - Etxabe, Julen; Izquierdo, Joseba; Landa, Aitor; Oiarbide, Mikel; Palomo, Claudio
Abstract 1H‐Imidazolones are reacted with nitroolefines and vinyl ketones in an enantioselective Michael reaction to trisubstituted amino acids.